Peran Variabel Kepercayaan dan Pengaruhnya Terhadap Loyalitas Konsumen Jasa Telekomuniasi GSM - Suyono Saputra; Yulfiswandi Yulfiswandi (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study explores the impact of brand experience, service quality, customer satisfaction, and trust on customer loyalty within the mobile telecommunications sector in Batam City. The participants of this research were residents of Batam who utilized cellular telecommunications services. Data was collected through an online questionnaire via Google Forms, targeting 300 respondents who were customers of mobile telecommunications services. The data analysis revealed several key findings: 1. A significant positive relationship exists between brand experience and customer loyalty. 2. Service quality is strongly linked to customer satisfaction. 3. There is a notable connection between brand experience and customer trust. 4. Customer satisfaction significantly influences customer loyalty.5. Service quality indirectly affects customer loyalty through customer satisfaction. 6. Interestingly, the study found no direct significant relationship between trust and loyalty, nor between brand experience and loyalty when mediated by trust. These results suggest that while brand experience, trust, and customer satisfaction are important factors influencing loyalty, trust does not directly contribute to building customer loyalty, nor does brand experience impact loyalty through trust. Moreover, maintaining high service quality is emphasized as a fundamental requirement for telecommunications service providers. This research provides valuable insights into the dynamics of customer loyalty in the mobile telecommunications context, offering practical implications for businesses in this industry aiming to enhance their customer retention strategies.